PENINGKATAN KELINCAHAN ATLET MELALUI PENGGUNAAN METODE KOMBINASI LATIHAN SIRKUITPLIOMETRIK DAN BERAT BADAN - Ismaryati Ismaryati (PAEDAGOGIA, 2008)
The main purpose of this research was to examine the effects of combinationcircuit-plyometric training method and body weight on agility. The method used in thisresearch was a field experiment using the 2x 2 (body weight x paining method) factorialdesigns. Eighty male students of Sport and Health Department of Teacher Training andEducation Faculty, Sebelas Maret University taken by purposive stratified randomsampling, were classified into four cells. The treatment was conducted three times a weekduring eight weeks. Body height and weight were measured with studio meter; agilitywith LSU Agility Obstacle Course, and the scores were recorded with photogate meter.Tests were administered prior to and after the eight week training program. The data wereanalyzed with two-way factorial ANOVA and Newman-Keuls test. The result of ANOVAand Newman-Keuls test from the combination circuit-plyometric skip jump hadsignificantly higher agility than combination circuit-plyometric squad jump trainingmethod. There was better average of increase on normal minus body weight than normalplus. There was significantly interaction into two-way between combination circuitplyometrictraining method and body weight. The group with normal minus body weightthat was trained by combination circuit-plyometric skip jump showed significantly betterresult than other groups.